Bedtime Use of Technology and Associated Sleep Problems in Children. (17th October 2017) - Fuller, Caitlyn; Lehman, Eric; Hicks, Steven; Novick, Marsha B.
Children comprise one of the largest consumer groups of technology. Sleep is fundamental to optimal functioning during childhood, including health and behavior. The purpose of this study was to explore bedtime electronic use and its impact on 3 health consequences—sleep quantity and quality, inattention, and body mass index. Parents of 234 children, ages 8 to 17 years, were surveyed to quantify hours of technology use (computer, video games, cell phone, and television), hours of sleep, and inattentive behaviors. Using any device at bedtime was associated with a statically significant increased use of multiple forms of technology at bedtime and use in the middle of the night, reducing sleep quantity and quality. Little association was found between technology use and inattention. A statistically significant association was found between bedtime technology use and elevated body mass index. Clinicians should discuss the impact of technology at bedtime to prevent harmful effects of overexposure.